Castleman′s disease - hyaline vascular type - clinical, cytological and histological features with review of literature - Ghosh Arnab; Pradhan Seema; Talwar O (Wolters Kluwer Medknow Publications, 2010)
Background and Aims: Castleman′s disease (CD) is a rare disease of lymph node with two identified forms - the hyaline vascular (HV) type or angiofollicular type and plasma cell (PC) type. It usually presents as localized or systemic lymphadenopathy or even as extra nodal mass and may give rise to several differential diagnoses. Fine needle aspiration cytology (FNAC), as the initial investigation, may be misleading. Excision biopsy usually gives the diagnosis. This study analyzes the clinical, cytological and histological features of CD of HV type Materials and Methods: All the cases of CD reported between 2001 and March 2008 have been reviewed. Cytology and histopathology slides of all cases were reviewed by two reporting pathologists independently and the clinical records were analyzed. Result: We had five cases of CD all of which presented as cervical lymphadenopathy of 1 to 5 cms in young patients. Patients were mostly asymptomatic with all relevant investigations within normal limits. The cytology findings mostly showed a predominance of small lymphocytes with capillary fragments. On excision biopsy, all cases were diagnosed as CD of HV type. Conclusion: CD should be kept as a differential of lymphadenopathy, especially in asymptomatic and young patients.